Implementasi Kebijakan Pendidikan Karakter di MTs Salafiyah Simbang Kulon II Pekalongan : Studi Analisis SWOT - Mohamad Siroj; Muhlisin, Muhlisin; Moh. Nasrudin (Jurnal Intelek Insan Cendikia, 2024)
This study aims to analyze the implementation of character education policy at MTs Salafiyah Simbang Kulon II Pekalongan using a SWOT approach (Strengths, Weaknesses, Opportunities, Threats). The results indicate that the school has strengths in its commitment to character education and the integration of religious values in learning. However, weaknesses include a lack of teacher training and limited time allocation. Opportunities that can be leveraged include government policy support and the use of digital technology, while the main threats are the negative influence of social media and rapid social change. This study recommends strengthening teacher training, collaborating with the community, and technology-based innovation to enhance the effectiveness of character education.